1999
DOI: 10.1086/313468
|View full text |Cite
|
Sign up to set email alerts
|

Skin Hygiene and Infection Prevention: More of the Same or Different Approaches?

Abstract: The purpose of this article is to review research indicating a link between hand hygiene and nosocomial infections and the effects of hand care practices on skin integrity and to make recommendations for potential changes in clinical practice and for further research regarding hand hygiene practices. Despite some methodological flaws and data gaps, evidence for a causal relationship between hand hygiene and reduced transmission of infections is convincing, but frequent handwashing causes skin damage, with resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
137
0
16

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(153 citation statements)
references
References 92 publications
(84 reference statements)
0
137
0
16
Order By: Relevance
“…Some experts may refer to the action of de-germing with detergent-based antiseptics or alcohol. 1 Hygienic hand rub consists in rubbing hands with a small quantity (2-3 mL) of a highly effective and fast-acting antiseptic agent.…”
Section: E F I N I T I O N Smentioning
confidence: 99%
See 1 more Smart Citation
“…Some experts may refer to the action of de-germing with detergent-based antiseptics or alcohol. 1 Hygienic hand rub consists in rubbing hands with a small quantity (2-3 mL) of a highly effective and fast-acting antiseptic agent.…”
Section: E F I N I T I O N Smentioning
confidence: 99%
“…These issues recently were reviewed in detail by Elaine Larson. 1 The need for ready access to hand-hygiene supplies, whether sink, soap, medicated detergent, or waterless alcohol-based hand-rub solution, is self-evident. Asking busy HCWs to walk away from the patient bed to reach a wash basin or to get a hand antisepsis solution invites noncompliance with hand-hygiene recommendations.…”
Section: Compliance W I T H H a N D H Y G I E N Ementioning
confidence: 99%
“…Hand hygiene education 60,140,334,429,648,651,666,676,684,686,687,698,705,707,708,[714][715][716][717]813,814,819,851,858 3. Promote/facilitate skin care for HCWs' hands 60,180,608,609 4. Routine observation and feedback 60,334,651,657,665,676,684,686,687,715,716,858 5.…”
Section: Marketing Technology For Hand Hygiene Promotionmentioning
confidence: 99%
“…58,179,180 In what would be considered an intervention trial using historical controls, Semmelweis 179 demonstrated in 1847 that the mortality rate among mothers delivering at the First Obstetrics Clinic at the General Hospital of Vienna was significantly lower when hospital staff cleaned their hands with an antiseptic agent than when they washed their hands with plain soap and water.…”
mentioning
confidence: 99%
“…Dr Elaine Larson published an extensive review of this topic recently and concluded that despite some methodological flaws and data gaps, evidence for a causal relationship between hand hygiene and reduced transmission of infections is convincing. But she also concluded that frequent handwashing causes skin damage, with resultant changes in microbial flora, increased skin shedding, and increased risk of microorganism transmission, suggesting that some traditional hand hygiene practices need reexamination (Larson 1999).…”
Section: Antimicrobials In Soapsmentioning
confidence: 99%